2016
DOI: 10.5209/rgid.54707
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del estado de la declaración de obras huérfanas en Europa

Abstract: Resumen. La Directiva europea 2012/28/UE sobre usos autorizados de obras huérfanas promueve la adopción por parte de los Estados miembros de las medidas necesarias para asegurar que la información sobre obras huérfanas se registre en una base de datos única para todos los estados de la Unión Europea. En octubre de 2014, la Oficina de Propiedad Intelectual de la Unión Europea (EUIPO) puso en marcha esta base de datos con el objetivo de recopilar toda la información relevante sobre obras huérfanas que poseen las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The results obtained by multiple research teams [5][6][7] have confirmed through relevant evidence that only the United Kingdom has set up detailed procedures or guidelines to deal with diligent searches about orphan works.…”
Section: Statutory Exception-based Modelmentioning
confidence: 52%
See 4 more Smart Citations
“…The results obtained by multiple research teams [5][6][7] have confirmed through relevant evidence that only the United Kingdom has set up detailed procedures or guidelines to deal with diligent searches about orphan works.…”
Section: Statutory Exception-based Modelmentioning
confidence: 52%
“…In the United States, this principle is governed by Title 17 of the Copyright Law and is being used as an effective solution for the problem posed by orphan works 3 . Cultural institutions wishing to engage in digitisation projects must rely on fair use to make their documentary heritage available on line.…”
Section: Fair Usementioning
confidence: 99%
See 3 more Smart Citations